Pengaruh Pengorbanan Nasabah (Customers’Sacrifice) dan Kualitas Pelayanan terhadap Kepuasan dan Loyalitas Nasabah (Studi pada Nasabah Funding BII Maybank Kantor Cabang Malang) - Hellyani, Catharina Aprilia; Rohman, Fatchur; Andarwati (Universitas Brawijaya, Indonesia, 2013)
This research aims to examine and confirm empirical evidence on: (1) the impact of Customer Sacrifice towards Customer Satisfaction on BII Maybank Malang Branch. (2) the impact of Service Quality towards Customer Satisfaction on BII Maybank Malang Branch. (3) the impact of Customer Satisfaction toward Customer Loyalty on BII Maybank Malang Branch. Practically, the results of this research are expected to be usable for BII Maybank management particularly in Malang Branch as a guidance or reference in making banking services policy or program innovations that attract customers. The research population is BII Maybank Malang Branch's customers that have joined the bank for at least 1 year and still have an active account. The number of sample is 80 respondents. The respondents are chosen by using nonprobability sampling called as purposive sampling technique. Method analysis used in this research is GSCA analysis. The result of this research indicates that: (1) Customer Sacrifice has negative but significant impact on Customer Satisfaction. (2) Service Quality has positive and significant impact on Customer Satisfaction. (3) Customer Satisfaction has positive and significant impact on Customer Loyalty.